Linking Boundaryless Career Orientation and Career Optimism: The Moderating Role of Career Decision Self-Efficacy and Career Adaptability - Silalahi, Santa Grace Meybiola; Andi Ina Yustina; Hajanirina, Andrianantenaina (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study examines the relationship between boundaryless career orientation and career optimism. Researchers tested and explored the possible moderating roles of both variables, namely career decision self-efficacy and career adaptability to the boundaryless career orientation and career optimism relationship. The survey was conducted on 192 accounting students in Indonesia to collect data. This research uses Smart-PLS to process and analyze data. The results showed that boundaryless career orientation is positively associated with career optimism. In this study, it was also shown that career decision self-efficacy and career adaptability successfully moderated the relationship between boundaryless career orientation and career optimism.